How one-parent-one-language strategy influences the development of balanced bilingualism - Lee, Debbie Shih Min (2017)
Despite the importance of attaining balanced development in both English and Mother Tongue, there is diminishing interest and usage of the latter among younger generations of Singaporeans. To address this issue, this paper aimed to investigate whether the One-Parent- One-Language (OPOL) strategy would promote the development of balanced bilingualism. An analysis of multiple case studies of parents who have adopted the OPOL strategy on their children garnered mixed results. Therefore, this paper further explored three main factors which could potentially influence the outcome of the OPOL strategy. The three factors are 1) interaction style of parents, 2) discourse strategies used by parents, and 3) environmental input. Other potential factors which have been briefly studied were also discussed. This paper has provided a better theoretical understanding regarding the effects of the OPOL strategy on balanced bilingualism. Based on the findings, a set of practical guidelines has also been developed to aid parents in the implementation of the OPOL strategy in their homes. However, the research studies examined in this literature review had their limitations, thus, further research is warranted before more definite conclusions can be drawn.